Globalization and Capitalist Geopolitics: Sovereignty and State Power in a Multipolar World - Daniel Woodley (Routledge, 2015)
FROM THE BACK COVER: Globalization and Capitalist Geopolitics is concerned with the growth of transnational corporate power against the backdrop of the decline of the West and the struggle by non-Western states to challenge and overcome domination of the rest of the world by the West. At the centre of the study is the problematic status of the US as guarantor of global security and imperial nation in decline. The declining power of America in a multipolar world places a question mark under the future of Western leadership of globalization. Woodley interrogates the structure of contemporary world order and examines competing approaches to globalization and global capitalism in international relations and international political economy. He engages with key scholars in the field, and provides an authoritative yet accessible commentary on debates on globalization and geopolitics in the wake of the global financial crisis. In a period of increasing geopolitical insecurity and geoeconomic transition, this book is a major contribution to the debate on globalization. It is a key resource for students and scholars seeking a deeper understanding of the historical and economic determinants of neoliberal capitalism, the impact of global economic convergence for Western economies, and the implications of globalization for the reconstruction of contemporary world order.
Additional information: This book is available on OAPEN: http://www.oapen.org/record/625755
Keywords: 330; capital as power; globalization; sovereignty; state power